Cytopenia among CML Patients on Imatinib in Kenya: Types, Grades, and Time Course - Angela McLigeyo; Jamilla Rajab; Mohammed Ezzi; Peter Oyiro; Yatich Bett; Andrew Odhiambo; Matilda Ong’ondi; Sitna Mwanzi; Mercy Gatua; NAOthieno- Abinya (Advances in Hematology)
Background. Imatinib mesylate is the gold standard for the treatment of all phases of Philadelphia-positive chronic myeloid leukemia. Patients on imatinib treatment may develop cytopenia due to drug toxicity. This study aimed to determine the types, grades, and time course of cytopenia in CML patients on imatinib at a Nairobi hospital. Methods. This was a cross-sectional descriptive study of adult patients aged ≥18 years followed up at the Glivec International Patient Access Program (GIPAP) clinic from 2007 to 2015. Patients who developed cytopenia within 12 months of initiating imatinib were eligible. Clinical and hematologic data were retrieved from the patients’ charts and entered into a study proforma. Measures of central tendency such as mean, median, mode, standard deviation, and variance were used for analysis. Results. Sixty three percent (63.6%) of the 94 patients developed a monocytopenia, with anemia seen in 34%, neutropenia in 27.6%, and thrombocytopenia in 8% of the 94 patients. Anemia plus neutropenia was the most common bicytopenia at 12.7%. Pancytopenia was seen in only 5 of the 94 patients. Most of the cytopenia was grades 2 and 3. Anemia was present at baseline while neutropenia and thrombocytopenia developed within 12 months of imatinib initiation. Anemia resolved during the first 12 months of therapy while neutropenia and thrombocytopenia resolved within 24–36 months of treatment. Conclusion. Monocytopenia, especially anemia, was the most common type of cytopenia. The cytopenia was predominantly grade 2, developed in majority of the patients within 6 months after imatinib initiation, and had resolved by 24–36 months after imatinib initiation.